Indirect brazing method for surface pre-metallized Y2O3-MgO ceramic and metal

By preparing the Ag-CuO-Al2O3 cladding layer on the surface of Y2O3-MgO ceramics, the metallurgical combination of ceramics and metals is achieved, and the problem of low brazing quality between Y2O3-MgO ceramics and metals is solved, and a high-strength brazing joint is obtained. Meet the high temperature and high intensity needs of the aircraft.

CN119187745AActive Publication Date: 2024-12-27HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411370429.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Y2O3-MgO nano-complex ceramics and metals are difficult to undergo metallurgical reaction and wetting, resulting in low brazing quality and difficult to meet the aircraft's high temperature and high strength requirements for infrared windows and metal connections.

Method used

Using the indirect brazing method of surface premetalization, Ag-CuO-Al2O3 cladding layer is prepared on the surface of Y2O3-MgO ceramics, and CuO and Al2O3 react with Y2O3 and MgO to form a metallization reaction layer, achieving good ceramics and metals. Metallurgical bonding and reliable connections are formed during vacuum brazing.

Benefits of technology

A defect-free brazed joint with good metallurgical bond was obtained, and the room temperature shear strength reached 67MPa, meeting the high strength requirements of the aircraft for connecting joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187745A_ABST
    Figure CN119187745A_ABST
Patent Text Reader

Abstract

The invention discloses an indirect brazing method for surface pre-metallized Y2O3-MgO ceramic and metal, and relates to a brazing method for Y2O3-MgO ceramic and metal. The invention aims to solve the problem that the Y2O3-MgO nano-composite ceramic and the metal brazing filler metal are difficult to generate metallurgical reaction and wetting. According to the method, the Ag-CuO-Al2O3 cladding layer is prepared on the to-be-welded surface of the Y2O3-MgO ceramic to achieve pre-metallization, active principal elements CuO and Al2O3 in the Ag-CuO-Al2O3 cladding layer react with Y2O3 and MgO respectively to generate a metallization reaction layer, so that the Ag-CuO-Al2O3 can be completely laid on the surface of the Y2O3-MgO ceramic, and metallurgical bonding with a good interface is achieved. In the vacuum brazing process, the Ag-based brazing filler metal can be reliably connected with metal on the other side while being well combined with the Ag-CuO-Al2O3 cladding layer, and therefore a brazed joint which is good in metallurgical bonding and free of defects is obtained. The room-temperature shear strength of a connection joint obtained through indirect brazing of the Y2O3-MgO ceramic and the metal reaches 67 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a brazing method for Y2O3-MgO ceramics and metal. Background Art

[0002] The infrared window is an important navigation device component of the aircraft. The increase in the flight speed of the aircraft has put forward higher requirements on the high temperature resistance and impact resistance of its infrared window. However, traditional infrared wave-transmitting materials often have the problems of strong spontaneous radiation at high temperature and serious loss of mechanical properties. Y2O3-MgO composite ceramics have the potential for high-temperature applications due to their good high-temperature infrared wave transmittance, mechanical strength and thermal shock resistance. In the future, they are expected to be widely used in the field of ultra-high-speed aircraft such as drones. However, in practical applications, it is often necessary to connect the infrared window with the metal to form a heterogeneous structure, so as to give full play to the advantages of ceramics and metals. Since the connection between the infrared window and the metal shell is susceptible to large aerodynamic and aerodynamic heat during the high-speed flight of the drone, higher requirements are put forward on the reliability of the joint between the Y2O3-MgO composite ceramic and the metal.

[0003] At present, there are few reports on the connection methods of Y2O3-MgO ceramics and metals. Since Y2O3-MgO ceramics are very brittle and it is difficult to machine complete mechanical holes, bolt connections are not suitable. The service temperature of adhesive joints generally does not exceed 200°C, which is difficult to meet the requirements of aircraft speed increase. Among the many welding methods, fusion welding methods are difficult to overcome the problems of Y2O3-MgO ceramics having a high melting point and a large difference from the melting point of metals. Pressure welding methods are difficult to adapt to the curved surface and thin-walled structure of infrared windows. In contrast, brazing is the most suitable connection method for Y2O3-MgO ceramic infrared windows.

[0004] However, since the metal oxide ceramics are mainly composed of covalent bonds and ionic bonds, they show very stable electronic coordination and stable chemical properties. In particular, among many metal oxides such as SiO2, Al2O3, CaO, ZrO2, and Y2O3, Y2O3 has the highest thermodynamic stability. Therefore, Y2O3-MgO nanocomposite ceramics with Y2O3 and MgO as the main components are difficult to react metallurgically with traditional metal brazing filler metals and form good wetting, thus affecting the brazing quality. Summary of the invention

[0005] In order to solve the problem that Y2O3-MgO nanocomposite ceramics and metal brazing filler metals are difficult to react and wet, the present invention provides an indirect brazing method for surface pre-metallized Y2O3-MgO ceramics and metals.

[0006] The indirect brazing method of the surface pre-metallized Y2O3-MgO ceramic and metal of the present invention is carried out according to the following steps:

[0007] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0008] The Y2O3-MgO ceramic is subjected to step-by-step grinding and ultrasonic cleaning of the surface to be welded in sequence;

[0009] 2. Pre-welding treatment of metal:

[0010] The metal surface to be welded is polished and ultrasonically cleaned in sequence;

[0011] 3. Preparation of cladding materials:

[0012] Weigh Ag powder, CuO powder and Al2O3 powder, mix them and then ball mill them to obtain Ag-CuO-Al2O3 cladding material;

[0013] The molar concentration of CuO in the Ag-CuO-Al2O3 cladding material is 2-40%, and the molar concentration of Al2O3 is 4-16%;

[0014] 4. Preparation of Y2O3-MgO ceramic surface cladding layer:

[0015] The Ag-CuO-Al2O3 cladding material obtained in step 3 is dissolved in anhydrous ethanol to obtain an Ag-CuO-Al2O3 cladding slurry, which is then evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and transferred to a muffle furnace for sintering to obtain an Ag-CuO-Al2O3 cladding layer on the surface of the Y2O3-MgO ceramic to be welded;

[0016] The mass fraction of the Ag-CuO-Al2O3 cladding material in the Ag-CuO-Al2O3 cladding slurry is 10-50%;

[0017] The sintering process is as follows: heating to 1000-1100°C at a heating rate not exceeding 5°C / min, keeping the temperature for 10-30min, and cooling to room temperature at a cooling rate not exceeding 5°C / min; the heating and cooling rates are both not exceeding 5°C / min to avoid excessive residual stress of the Y2O3-MgO ceramics that affects the performance of the joint and even causes ceramic cracking;

[0018] 5. Pre-treatment of silver-based solder foil:

[0019] The silver-based solder foil is cut to a predetermined size, and then both surfaces of the silver-based solder foil are polished, and finally ultrasonically cleaned;

[0020] 6. Assembly of welding specimens:

[0021] The silver-based solder foil is placed between the Y2O3-MgO ceramic surface cladding layer and the metal surface to be welded, and is fixed by a fixture to obtain an assembly;

[0022] 7. Vacuum brazing: Place the assembled parts into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of the surface pre-metallized Y2O3-MgO ceramic and the metal;

[0023] The vacuum brazing process is as follows: the vacuum degree in the vacuum brazing furnace does not exceed 8×10 -3 Pa, the heating rate does not exceed 15℃ / min, the brazing temperature is 840℃~900℃, the holding time is 10min~40min, and the temperature is cooled to room temperature after the holding period, and the cooling rate does not exceed 10℃ / min.

[0024] The principles and beneficial effects of the present invention are:

[0025] The present invention realizes pre-metallization by preparing an Ag-CuO-Al2O3 cladding layer on the surface of the Y2O3-MgO ceramic to be welded, thereby avoiding the problem of poor metallurgical reaction between the traditional metal brazing filler metal and the Y2O3-MgO ceramic, resulting in low quality of the welded joint. The present invention uses CuO and Al2O3 in the Ag-CuO-Al2O3 cladding layer as active main elements to react with Y2O3 and MgO respectively to generate a metallization reaction layer, the composition of which is Y2Cu2O5, Mg 0.8 Cu 0.2 O and Y4Al2O9 achieve good metallurgical bonding with the ceramic side interface, thereby realizing a metallization process based on Ag on the surface of the Y2O3-MgO ceramic. During the vacuum brazing process, the brazing material not only achieves good bonding with the Ag-CuO-Al2O3 cladding layer, but also forms a reliable connection with the metal on the other side, thereby obtaining a brazed joint with good metallurgical bonding and no defects. The room temperature shear strength of the connection joint obtained by indirect brazing of the Y2O3-MgO ceramic and the metal of the present invention reaches 67MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a microstructure picture of the brazed joint obtained in Example 1;

[0027] Figure 2 The microstructure diagram and element surface scanning diagram of the ceramic side reaction layer of the brazed joint obtained in Example 1;

[0028] Figure 3 This is a microstructure picture of the brazed joint obtained in Example 2. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0030] Specific implementation method 1: In this implementation method, the indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal is carried out according to the following steps:

[0031] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0032] The Y2O3-MgO ceramic is subjected to step-by-step grinding and ultrasonic cleaning of the surface to be welded in sequence;

[0033] 2. Pre-welding treatment of metal:

[0034] The metal surface to be welded is polished and ultrasonically cleaned in sequence;

[0035] 3. Preparation of cladding materials:

[0036] Weigh Ag powder, CuO powder and Al2O3 powder, mix them and then ball mill them to obtain Ag-CuO-Al2O3 cladding material;

[0037] The molar concentration of CuO in the Ag-CuO-Al2O3 cladding material is 2-40%, and the molar concentration of Al2O3 is 4-16%;

[0038] 4. Preparation of Y2O3-MgO ceramic surface cladding layer:

[0039] The Ag-CuO-Al2O3 cladding material obtained in step 3 is dissolved in anhydrous ethanol to obtain an Ag-CuO-Al2O3 cladding slurry, which is then evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and transferred to a muffle furnace for sintering to obtain an Ag-CuO-Al2O3 cladding layer on the surface of the Y2O3-MgO ceramic to be welded;

[0040] The mass fraction of the Ag-CuO-Al2O3 cladding material in the Ag-CuO-Al2O3 cladding slurry is 10-50%;

[0041] The sintering process is as follows: heating to 1000-1100°C at a heating rate not exceeding 5°C / min, keeping the temperature for 10-30min, and cooling to room temperature at a cooling rate not exceeding 5°C / min; the heating and cooling rates are both not exceeding 5°C / min to avoid excessive residual stress of the Y2O3-MgO ceramics that affects the performance of the joint and even causes ceramic cracking;

[0042] 5. Pre-treatment of silver-based solder foil:

[0043] The silver-based solder foil is cut to a predetermined size, and then both surfaces of the silver-based solder foil are polished, and finally ultrasonically cleaned;

[0044] 6. Assembly of welding specimens:

[0045] The silver-based solder foil is placed between the Y2O3-MgO ceramic surface cladding layer and the metal surface to be welded, and is fixed by a fixture to obtain an assembly;

[0046] 7. Vacuum brazing: Place the assembled parts into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of the surface pre-metallized Y2O3-MgO ceramic and the metal;

[0047] The vacuum brazing process is as follows: the vacuum degree in the vacuum brazing furnace does not exceed 8×10 -3 Pa, the heating rate does not exceed 15℃ / min, the brazing temperature is 840℃~900℃, the holding time is 10min~40min, and the temperature is cooled to room temperature after the holding period, and the cooling rate does not exceed 10℃ / min.

[0048] In this embodiment, the Ag-CuO-Al2O3 cladding layer is prepared on the surface of the Y2O3-MgO ceramic to be welded to achieve pre-metallization, thereby avoiding the problem of poor metallurgical reaction between the traditional metal brazing filler metal and the Y2O3-MgO ceramic, resulting in low quality of the welded joint. In this embodiment, CuO and Al2O3 in the Ag-CuO-Al2O3 cladding layer are used as active main elements to react with Y2O3 and MgO respectively to generate a metallization reaction layer. The composition of the metallization reaction layer is Y2Cu2O5, Mg 0.8 Cu 0.2 O and Y4Al2O9 achieve good metallurgical bonding with the ceramic side interface, thereby realizing a metallization process based on Ag on the surface of the Y2O3-MgO ceramic. During the vacuum brazing process, the brazing material not only achieves good bonding with the Ag-CuO-Al2O3 cladding layer, but also forms a reliable connection with the metal on the other side, thereby obtaining a brazed joint with good metallurgical bonding and no defects. The room temperature shear strength of the connection joint obtained by indirect brazing of the Y2O3-MgO ceramic and the metal of the present invention reaches 67MPa.

[0049] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: in step 1, 400-3000 mesh diamond sandpaper is used for the step-by-step grinding of the surface to be welded.

[0050] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the ultrasonic cleaning time in step one is 5-60 minutes, and the cleaning agent used is anhydrous ethanol or acetone.

[0051] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: in step 2, the metal surface to be welded is polished using 400-3000 mesh sandpaper.

[0052] Specific implementation method five: This implementation method is different from any one of specific implementation methods one to four in that: the ultrasonic cleaning time of the metal surface to be welded in step two is 5-60 minutes, and the cleaning agent used is anhydrous ethanol or acetone.

[0053] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that: the metal in step 2 is titanium alloy, titanium aluminum alloy or niobium.

[0054] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 1 to 6 in that: the ball milling time in step 3 is 2-12 hours.

[0055] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the duration of each ultrasonic cleaning in step five is 5 to 60 minutes, the frequency is 80 to 120 kHz, and the cleaning is repeated 2 to 5 times.

[0056] Specific implementation method 9: This implementation method is different from any one of specific implementation methods 1 to 8 in that: the cleaning agent used in the ultrasonic cleaning in step 5 is anhydrous ethanol or acetone.

[0057] Specific implementation method ten: This implementation method is different from any one of specific implementation methods one to nine in that: in step five, 400-3000 mesh sandpaper is used to polish the two surfaces of the silver-based solder foil.

[0058] Specific embodiment eleven: This embodiment differs from specific embodiments one to ten in that the silver-based solder foil is Ag-Cu solder foil, Ag-Cu-In solder foil, Ag-Cu-Ni solder foil or Ag-Cu-Ti solder foil.

[0059] Embodiment 1:

[0060] The indirect brazing method of the surface pre-metallized Y2O3-MgO ceramic and metal in this embodiment is carried out according to the following steps:

[0061] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0062] The 4mm×4mm×3mm Y2O3-MgO ceramics were subjected to step-by-step grinding and ultrasonic cleaning of the surface to be welded;

[0063] The step-by-step grinding of the surface to be welded uses 400#, 800#, 1500#, and 2000# diamond sandpaper;

[0064] The ultrasonic cleaning time is 20 minutes, and the cleaning agent used is anhydrous ethanol;

[0065] 2. Pre-welding treatment of metal:

[0066] The metal surface to be welded of 15 mm × 10 mm × 3 mm was polished and ultrasonically cleaned in sequence;

[0067] The metal surface to be welded is polished with 1500-grit sandpaper;

[0068] The ultrasonic cleaning time of the metal surface to be welded is 20 minutes, and the cleaning agent used is anhydrous ethanol;

[0069] The metal is TC4 alloy;

[0070] 3. Preparation of cladding materials:

[0071] Weigh Ag powder, CuO powder and Al2O3 powder, mix them and then ball mill them to obtain Ag-CuO-Al2O3 cladding material;

[0072] The ball milling time is 7h;

[0073] The molar concentration of CuO in the Ag-CuO-Al2O3 cladding material is 24%, and the molar concentration of Al2O3 is 8%;

[0074] 4. Preparation of Y2O3-MgO ceramic surface cladding layer:

[0075] The Ag-CuO-Al2O3 cladding material obtained in step 3 is dissolved in anhydrous ethanol to obtain an Ag-CuO-Al2O3 cladding slurry, which is then evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and transferred to a muffle furnace for sintering to obtain an Ag-CuO-Al2O3 cladding layer on the surface of the Y2O3-MgO ceramic to be welded;

[0076] The mass fraction of the Ag-CuO-Al2O3 cladding material in the Ag-CuO-Al2O3 cladding slurry is 30%;

[0077] The sintering process is as follows: heating to 1000°C at a heating rate of 5°C / min, keeping the temperature for 30 minutes, and cooling to room temperature at a cooling rate of 5°C / min;

[0078] 5. Pre-treatment of silver-based solder foil:

[0079] The silver-based solder foil was cut into 6 mm × 6 mm, and then both surfaces of the silver-based solder foil were polished and finally ultrasonically cleaned;

[0080] The silver-based solder foil is an Ag-Cu solder foil, and the mass ratio of Ag to Cu is 72:28;

[0081] The ultrasonic cleaning time was 10 min each time, the frequency was 100 kHz, and the cleaning was repeated 3 times, and the cleaning agent used was anhydrous ethanol;

[0082] The two surfaces of the silver-based solder foil are polished with 1000-grit sandpaper;

[0083] 6. Assembly of welding specimens:

[0084] The silver-based solder foil is placed between the Y2O3-MgO ceramic surface cladding layer and the metal surface to be welded, and is fixed by a fixture to obtain an assembly;

[0085] 7. Vacuum brazing: Place the assembled parts into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of the surface pre-metallized Y2O3-MgO ceramic and the metal;

[0086] The vacuum brazing process is as follows: the vacuum degree in the vacuum brazing furnace is 3×10 -5 Pa, heating rate is 10℃ / min, brazing temperature is 860℃, holding time is 20min, after holding, cool to room temperature, cooling rate is 5℃ / min.

[0087] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. The room temperature shear strength of the connection joint obtained in this embodiment reached 67 MPa.

[0088] Figure 1 The microstructure picture of the brazed joint obtained in Example 1 is shown in FIG. Figure 1 It can be seen that the indirect brazing joint obtained in this embodiment generates an obvious reaction layer on the ceramic side, indicating that the metallurgical bonding is good during the pre-metallization process and no defects are generated in the joint as a whole. Figure 2 The microstructure diagram and elemental surface scanning diagram of the ceramic side reaction layer of the brazed joint obtained in Example 1; Table 1 is the EDS analysis results (at.%) of each phase. Figure 2 As shown in Table 1, the dark black phase is Mg 0.8 Cu 0.2 O compounds, and are distributed in the Y2Cu2O5 layer in a dotted manner, while Y4Al2O9 is distributed between Y2Cu2O5 and Mg 0.8 Cu 0.2 O outside, indicating that the ceramic side interface has achieved good metallurgical bonding.

[0089] Table 1

[0090]

[0091] Embodiment 2:

[0092] The indirect brazing method of the surface pre-metallized Y2O3-MgO ceramic and metal in this embodiment is carried out according to the following steps:

[0093] 1. Pre-welding treatment of Y2O3-MgO ceramics:

[0094] The 4mm×4mm×3mm Y2O3-MgO ceramics were subjected to step-by-step grinding and ultrasonic cleaning of the surface to be welded;

[0095] The step-by-step grinding of the surface to be welded uses 400#, 800#, 1500#, and 2000# diamond sandpaper;

[0096] The ultrasonic cleaning time is 20 minutes, and the cleaning agent used is anhydrous ethanol;

[0097] 2. Pre-welding treatment of metal:

[0098] The metal surface to be welded of 15 mm × 10 mm × 3 mm was polished and ultrasonically cleaned in sequence;

[0099] The metal surface to be welded is polished with 1500-grit sandpaper;

[0100] The ultrasonic cleaning time of the metal surface to be welded is 20 minutes, and the cleaning agent used is anhydrous ethanol;

[0101] The metal is TC4 alloy;

[0102] 3. Preparation of cladding materials:

[0103] Weigh Ag powder, CuO powder and Al2O3 powder, mix them and then ball mill them to obtain Ag-CuO-Al2O3 cladding material;

[0104] The ball milling time is 7h;

[0105] The molar concentration of CuO in the Ag-CuO-Al2O3 cladding material is 32%, and the molar concentration of Al2O3 is 6%;

[0106] 4. Preparation of Y2O3-MgO ceramic surface cladding layer:

[0107] The Ag-CuO-Al2O3 cladding material obtained in step 3 is dissolved in anhydrous ethanol to obtain an Ag-CuO-Al2O3 cladding slurry, which is then evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and transferred to a muffle furnace for sintering to obtain an Ag-CuO-Al2O3 cladding layer on the surface of the Y2O3-MgO ceramic to be welded;

[0108] The mass fraction of the Ag-CuO-Al2O3 cladding material in the Ag-CuO-Al2O3 cladding slurry is 30%;

[0109] The sintering process is as follows: heating to 1000°C at a heating rate of 5°C / min, keeping the temperature for 30 minutes, and cooling to room temperature at a cooling rate of 5°C / min;

[0110] 5. Pre-treatment of silver-based solder foil:

[0111] The silver-based solder foil was cut into 6 mm × 6 mm, and then both surfaces of the silver-based solder foil were polished and finally ultrasonically cleaned;

[0112] The silver-based solder foil is an Ag-Cu solder foil, and the mass ratio of Ag to Cu is 72:28;

[0113] The ultrasonic cleaning time was 10 min each time, the frequency was 100 kHz, and the cleaning was repeated 3 times, and the cleaning agent used was anhydrous ethanol;

[0114] The two surfaces of the silver-based solder foil are polished with 1000-grit sandpaper;

[0115] 6. Assembly of welding specimens:

[0116] The silver-based solder foil is placed between the Y2O3-MgO ceramic surface cladding layer and the metal surface to be welded, and is fixed by a fixture to obtain an assembly;

[0117] 7. Vacuum brazing: Place the assembled parts into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of the surface pre-metallized Y2O3-MgO ceramic and the metal;

[0118] The vacuum brazing process is as follows: the vacuum degree in the vacuum brazing furnace is 3×10 -5 Pa, heating rate is 10℃ / min, brazing temperature is 880℃, holding time is 20min, cooling to room temperature after holding, cooling rate is 5℃ / min.

[0119] The shear test was carried out using an electronic universal testing machine with a loading speed of 0.5 mm / min. The room temperature shear strength of the connection joint obtained in this embodiment reached 60 MPa. Figure 3 The microstructure picture of the brazed joint obtained in Example 2 is shown in FIG. Figure 3 It can be seen that the indirect brazing joint obtained in Example 2 generates an obvious reaction layer on the ceramic side, indicating that the metallurgical bonding is good during the pre-metallization process and no defects are generated in the joint as a whole.

Claims

1. An indirect brazing method for surface pre-metallized Y2O3-MgO ceramics and metals, characterized in that: The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal is carried out according to the following steps:

1. Pre-welding treatment of Y2O3-MgO ceramics: The Y2O3-MgO ceramic is subjected to step-by-step grinding and ultrasonic cleaning of the surface to be welded in sequence; 2. Pre-welding treatment of metal: The metal surface to be welded is polished and ultrasonically cleaned in sequence; 3. Preparation of cladding materials: Weigh Ag powder, CuO powder and Al2O3 powder, mix them and then ball mill them to obtain Ag-CuO-Al2O3 cladding material; The molar concentration of CuO in the Ag-CuO-Al2O3 cladding material is 2-40%, and the molar concentration of Al2O3 is 4-16%; 4. Preparation of Y2O3-MgO ceramic surface cladding layer: The Ag-CuO-Al2O3 cladding material obtained in step 3 is dissolved in anhydrous ethanol to obtain an Ag-CuO-Al2O3 cladding slurry, which is then evenly coated on the surface of the Y2O3-MgO ceramic to be welded, and transferred to a muffle furnace for sintering to obtain an Ag-CuO-Al2O3 cladding layer on the surface of the Y2O3-MgO ceramic to be welded; The mass fraction of the Ag-CuO-Al2O3 cladding material in the Ag-CuO-Al2O3 cladding slurry is 10-50%; The sintering process is as follows: heating to 1000-1100°C at a heating rate not exceeding 5°C / min, keeping the temperature for 10-30min, and cooling to room temperature at a cooling rate not exceeding 5°C / min; the heating and cooling rates are both not exceeding 5°C / min to avoid excessive residual stress of the Y2O3-MgO ceramics that affects the performance of the joint and even causes ceramic cracking; 5. Pre-treatment of silver-based solder foil: The silver-based solder foil is cut to a predetermined size, and then both surfaces of the silver-based solder foil are polished, and finally ultrasonically cleaned; 6. Assembly of welding specimens: The silver-based solder foil is placed between the Y2O3-MgO ceramic surface cladding layer and the metal surface to be welded, and is fixed by a fixture to obtain an assembly; 7. Vacuum brazing: Place the assembled parts into a vacuum brazing furnace for vacuum brazing to complete the indirect brazing of the surface pre-metallized Y2O3-MgO ceramic and the metal; The vacuum brazing process is as follows: the vacuum degree in the vacuum brazing furnace does not exceed 8×10 -3 Pa, the heating rate does not exceed 15℃ / min, the brazing temperature is 840℃~900℃, the holding time is 10min~40min, and the temperature is cooled to room temperature after the holding period, and the cooling rate does not exceed 10℃ / min.

2. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: In step 1, diamond sandpaper with a mesh size of 400 to 3000 is used for the step-by-step grinding of the surface to be welded.

3. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: The ultrasonic cleaning time in step 1 is 5-60 minutes, and the cleaning agent used is anhydrous ethanol or acetone.

4. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: In step 2, the metal surface to be welded is polished using 400-3000 grit sandpaper.

5. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: In step 2, the ultrasonic cleaning time of the metal surface to be welded is 5-60 minutes, and the cleaning agent used is anhydrous ethanol or acetone.

6. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: In step 2, the metal is titanium alloy, titanium aluminum alloy or niobium.

7. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: The ball milling time in step 3 is 2-12 hours.

8. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: The ultrasonic cleaning time of each step in step 5 is 5 to 60 minutes, the frequency is 80 to 120 kHz, and the cleaning is repeated 2 to 5 times.

9. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: The cleaning agent used in the ultrasonic cleaning in step 5 is anhydrous ethanol or acetone.

10. The indirect brazing method of surface pre-metallized Y2O3-MgO ceramic and metal according to claim 1, characterized in that: In step 5, the two surfaces of the silver-based solder foil are polished using 400-3000 grit sandpaper.

Citation Information

Patent Citations

  • Brazing method for porous ceramic and metal

    CN106944695A

  • Application of Cu-Ti brazing filler metal with high Cu atomic ratio in ceramic and metal brazing

    CN115476012A

  • Method for brazing Y2O3-MgO composite ceramic and metal by adopting TiZrNiCu active brazing filler metal

    CN117921118A

  • Method for brazed connection of Y2O3-MgO nano-composite ceramic and titanium alloy

    CN118492542A

  • Method of bonding a ceramic article to a metal article

    US4883217A